Diversification in the enterprises’ activities for sustainable development in the agricultural sector - Denysiuk, Olena; Svitlyshyn, Ihor; Tsaruk, Iryna; Vikarchuk, Olga; Dankevych, Andrii (My University, 2022)
The relevance of the study is determined by the need to develop and implement effective mechanisms for sustainable development of agricultural enterprise under current economic conditions, which allows solving the issues of public employment in rural areas and increasing the overall level of citizens' incomes in a qualitative way. The purpose of the study is to investigate the practical possibilities of developing the diversification of agricultural enterprises' activities, to assess the real prospects for stimulating their activities and increasing the overall level of organisation of the modern agricultural enterprises' functioning. The basis of methodological approach is the combination of methods for system analysis of the basis for implementing the diversification of the agricultural enterprises' activity with the analytical investigation of the prospects for the development of agricultural production in modern economic conditions. The results of this study indicate that there are multiple factors affecting the development of diversification in agricultural enterprises in relation to the nature of their activities and the type of commodity products they manufacture, as determined by the specifics of the market and its activity at given time intervals. The findings and conclusions of this study are of significant practical relevance to agricultural workers, whose professional responsibilities include the implementation of measures aimed at the diversification of agricultural enterprises, and the realisation of pre-designed programmes for the development of agricultural enterprises in a particular region or nation-wide. The aim is to increase the overall economic potential of the country, through the development of the agricultural sector

Актуальність дослідження зумовлена необхідністю розробки та впровадження ефективних механізмів сталого розвитку сільськогосподарського підприємства в сучасних економічних умовах, що дозволяє якісно вирішувати питання зайнятості населення на селі та підвищувати загальний рівень доходів громадян. спосіб. Мета дослідження – дослідити практичні можливості розвитку диверсифікації діяльності сільськогосподарських підприємств, оцінити реальні перспективи стимулювання їх діяльності та підвищення загального рівня організації функціонування сучасних сільськогосподарських підприємств. Основою методичного підходу є поєднання методів системного аналізу засад здійснення диверсифікації діяльності сільськогосподарських підприємств з аналітичним дослідженням перспектив розвитку сільськогосподарського виробництва в сучасних умовах господарювання. Результати проведеного дослідження свідчать про те, що на розвиток диверсифікації сільськогосподарських підприємств впливають численні фактори, які залежать від характеру їх діяльності та виду товарної продукції, що виробляється, що визначається специфікою ринку та його активністю в даний момент часу. інтервали. Результати та висновки цього дослідження мають важливе практичне значення для працівників сільського господарства, до професійних обов’язків яких входить реалізація заходів, спрямованих на диверсифікацію сільськогосподарських підприємств, реалізація заздалегідь розроблених програм розвитку сільськогосподарських підприємств окремого регіону. або загальнонаціональний. Метою є збільшення загального економічного потенціалу країни через розвиток аграрного сектору
Keywords: agriculture; agricultural production; diversification of agricultural activities; rural areas; development investments; business plan; sustainability; сільське господарство; сільськогосподарське виробництво; диверсифікація сільськогосподарської діяльності; сільські території; інвестиції розвитку; бізнес-план; сталий розвиток; кафедра економіки і права